PENGARUH PROPORSI KEJU CHEDDAR DAN PARMESAN TERHADAP SIFAT ORGANOLEPTIK CHEESE CASATO KROKET - Nur Wisanggeni Muhammad; Any Sutiadiningsih; Sri Handajani; Ila Huda Puspita Dewi (KAMPUS AKADEMIK PUBLISING, 2026)
The objective of this study was to expand the variety of delicious and healthy croquettes and to produce a croquette product. Specifically, the study aimed to assess the nutritional value of the best product and determine the effect of the amounts of Cheddar and Parmesan cheese on organoleptic characteristics. An experimental approach was employed in this study, evaluating Cheddar-to-Parmesan cheese ratios of 80:20, 70:30, and 60:40. The 60:40 ratio yielded the best results regarding taste, aroma, color, texture, and overall consumer preference. Laboratory analysis revealed that the Cheese Casato croquette contained 68.55% carbohydrates, 14.05% protein, 7.98% fat, and 0.13% sodium. All nutritional values met established quality standards for croquettes. In conclusion, the study successfully produced a product that was well-received by panelists and met nutritional standards, making it a promising product.